The risk of placenta accreta following primary elective caesarean delivery: a case–control study. Issue 7 (28th February 2013) - Kamara, M; Henderson, JJ; Doherty, DA; Dickinson, JE; Pennell, CE
<x xml:space="preserve">Abstract</x> Objective To evaluate the risk of placenta praevia accreta following primary (first) elective or primary emergency caesarean section in a pregnancy complicated by placenta praevia. Design Retrospective matched case–control study, employing variable matching. Setting Tertiary referral centre between 1993 and 2008. Population Sixty‐five cases and 102 controls were used for the analysis from a total of 82 667 births during the study period. Methods Relevant data were abstracted from clinical records. Matching of cases with controls was based on co‐existing placenta praevia, number of previous caesarean sections, and age, with one or two controls per case. Results are presented as odds ratios (ORs) with 95% confidence intervals (95% CIs). Main outcome measures Placenta accreta in a pregnancy complicated by placenta praevia following a primary elective or emergency caesarean section, and morbidity associated with pregnancies complicated by placenta accreta. Results Significantly more cases than controls had an elective caesarean section for their primary caesarean delivery (46.2 versus 18.6%; P < 0.001). There were no differences between groups for previous pregnancy loss, uterine surgery, and vaginal delivery, before or after the primary caesarean section. Compared with primary emergency caesarean section, primary elective caesarean section significantly increased the risk of placenta accreta in a subsequent pregnancy in the presence of placenta praevia (OR 3.00; 95% CI 1.47–6.12; P = 0.025). Conclusions Our results suggest that women with a primary elective caesarean section without labour are more likely, compared with those undergoing primary emergency caesarean section with labour, to develop an accreta in a subsequent pregnancy with placenta praevia.